2023
DOI: 10.3390/plants12183327
|View full text |Cite
|
Sign up to set email alerts
|

Botanical Collection Patterns and Conservation Categories of the Most Traded Timber Species from the Ecuadorian Amazon: The Role of Protected Areas

Rolando López-Tobar,
Robinson J. Herrera-Feijoo,
Rubén G. Mateo
et al.

Abstract: The Ecuadorian Amazon is home to a rich biodiversity of woody plant species. Nonetheless, their conservation remains difficult, as some areas remain poorly explored and lack georeferenced records. Therefore, the current study aims predominantly to analyze the collection patterns of timber species in the Amazon lowlands of Ecuador and to evaluate the conservation coverage of these species in protected areas. Furthermore, we try to determine the conservation category of the species according to the criteria of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 108 publications
(174 reference statements)
1
2
0
1
Order By: Relevance
“…Regarding the percentage of trees classified as LC species, this is similar to that reported by López-Tobar et al [55] who analyzed 214 of the most commercialized timber species in the Amazon and found that 67.6% (142 sp.) are currently classified as LC species.…”
Section: Speciessupporting
confidence: 88%
See 2 more Smart Citations
“…Regarding the percentage of trees classified as LC species, this is similar to that reported by López-Tobar et al [55] who analyzed 214 of the most commercialized timber species in the Amazon and found that 67.6% (142 sp.) are currently classified as LC species.…”
Section: Speciessupporting
confidence: 88%
“…This pattern of nonevaluated species is similar to that reported by Guevara et al [66] who in their findings highlight that 89% of the lowland tree species in the RAE have not been evaluated by the IUCN. Similarly, López-Tobar et al [55] suggest that 28% (60 sp.) of the most traded timber species in the last 10 years (2012-2021) do not have a current conservation category according to the latest IUCN red list update.…”
Section: Speciesmentioning
confidence: 86%
See 1 more Smart Citation
“…Las precipitaciones son copiosas, variando entre 3000 mm y 6000 mm anuales. Estas condiciones climáticas particulares no solo influyen en la biodiversidad y los ecosistemas locales (López-Tobar et al, 2023), sino también en la composición y descomposición de los residuos sólidos domiciliarios, aspectos cruciales para considerar en la gestión y tratamiento de los residuos en la región (Diéguez-Santana et al, 2017;Jaramillo et al, 2023;Peñafiel-Arcos et al, 2022)…”
Section: áRea De Estudiounclassified